2019
DOI: 10.1519/jpt.0000000000000159
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Physical Performance Outcome Measures Used in Exercise Interventions for Older Adults With Alzheimer Disease and Related Dementias

Abstract: The results of this review will aid clinicians and researchers in selecting reliable measures to evaluate physical performance outcomes in response to exercise interventions in older adults with ADRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 85 publications
2
38
0
1
Order By: Relevance
“…The few available investigations also focusing on recommendations of motor assessments in IWD analysed assessments used in previous trials from a quantitative perspective, and did not deal with standardisation of assessment procedures or tailoring assessments to specific characteristics of IWD. For the most part, the assessments recommended in this paper coincide with these recommendations (see Bossers et al [ 19 ] and McGough et al [ 31 ]).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The few available investigations also focusing on recommendations of motor assessments in IWD analysed assessments used in previous trials from a quantitative perspective, and did not deal with standardisation of assessment procedures or tailoring assessments to specific characteristics of IWD. For the most part, the assessments recommended in this paper coincide with these recommendations (see Bossers et al [ 19 ] and McGough et al [ 31 ]).…”
Section: Discussionmentioning
confidence: 58%
“…Unfortunately, there is currently a lack of recommendations or guidelines on how to assess motor performance in IWD. In two of the few studies addressing this issue, Bossers et al [ 19 ] and McGough et al [ 31 ] performed a systematic and scoping review, respectively, and recommended using the Berg Balance Scale, the Performance Oriented Mobility Assessment, the Timed Up & Go Test (TUG), short distance walk tests (WT), sit-to-stand (STS) tests, isometric strength assessments, and the 6-min WT for IWD in mild to moderate stages of the disease. Both research groups derived their recommendations based on frequency of use and observed outcome effect sizes in previous trials.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally to elaborating recommendations, this article emphasises the need for tailoring and standardising motor assessments for IWD [22]. Moreover, three systematic reviews [7, 13, 23] and one scoping review [24] examined frequency of use, sensitivity to change, and psychometric properties. Bossers et al [13] and McGough et al [24] identified eight frequently applied, sensitive assessments, showing good to excellent relative test-retest reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise as a therapeutic intervention (or clinical exercise) is the application of the body of knowledge of sports science involving physiological, metabolic, and structural responses and prescribing principles to short-and long-term PA with clinical relevance to the management of health conditions. 19,20 Clinical exercise is becoming extremely relevant as a new efficacious therapeutic intervention in multiple medical fields. Besides helping in disease management, clinical exercise also improves physical fitness and is associated with other general health benefits, including the improvement of cardio-and cerebrovascular health, reduction of osteoporosis and age-related sarcopenia, improvement in psychological and autonomic disorders, and as having a general anti-inflammatory effect.…”
Section: Exercise As a Therapeutic Interventionmentioning
confidence: 99%